2008
DOI: 10.1097/bsd.0b013e31815b5cc4
|View full text |Cite
|
Sign up to set email alerts
|

Ilio-lumbar Fixation—The Amrita Technique

Abstract: Our technique of ilio-lumbar fixation provides a stable and simple alternative to reconstruct potentially devastating instability of the lumbosacral junction. The 2 iliac screws, when used as described, make the procedure technically easier, reduce the hardware prominence without compromising the stability to construct and provide adequate bone graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…Iliac screw technique is a common technique adopted in treating certain typical conditions requiring long segment fixation such as in the correction of neuromuscular and adult scoliosis, reduction of high-grade spondylolisthesis, sacral fractures, and surgical treatment of sacral tumors requiring sacrectomy [1][2][3][4][5][6][7][8]. Although iliac screw fixation provides a solid foundation to restore spinal balance and to stabilize the lumbosacral junction, high rate of implant failure including screw loosening and breakage has also been reported, especially in patients with bilateral single iliac screw fixation [2,3,5,8].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Iliac screw technique is a common technique adopted in treating certain typical conditions requiring long segment fixation such as in the correction of neuromuscular and adult scoliosis, reduction of high-grade spondylolisthesis, sacral fractures, and surgical treatment of sacral tumors requiring sacrectomy [1][2][3][4][5][6][7][8]. Although iliac screw fixation provides a solid foundation to restore spinal balance and to stabilize the lumbosacral junction, high rate of implant failure including screw loosening and breakage has also been reported, especially in patients with bilateral single iliac screw fixation [2,3,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic and radiographic studies have confirmed that there are two columns in the upper and lower areas of the ilium where the cancellous bone is found in abundance [6,[9][10][11][12]. The upper iliac column stands from the posterior superior iliac spine (PSIS) to the highest portion of the iliac crest; the lower column is located in the area from PSIS to the anterior inferior iliac spine (AIIS).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations